The experience of small medium, and micro- enterprises (SMMEs) owners in improving opportunities through the adoption of Fintech services - Bogie, Jill (University of Pretoria, 2026)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2025.